The Impact of Community Service on Early Detection of Conenital Anomalies of the Kidney and Urinary Tract and Congenital Heart Disease in Children at Primary Health Care Sobo, Banyuwangi, Indonesia - Risky Vitria Prasetyo; Arief Rakhman Hakim; Fandaruzzahra Putri; Susianto, Steven Christian; Agus Budiarto; Muhammad Riza Kurniawan; Ninik Asmaningsih Soemyarso; Mohammad Sjaifullah Noer (Journal of Community Medicine and Public Health Research, 2025)
Congenital anomalies of the kidney and urinary tract (CAKUT) and congenital heart disease (CHD) represent significant global public health challenges, contributing substantially to childhood morbidity and mortality. This study aimed to determine the impact of the community service on CAKUT and CHD early detection conducted by Universitas Airlangga, Surabaya, Indonesia, at Puskesmas Sobo, Banyuwangi Regency. This pre-test post-test design study was conducted among health cadres, parents of students, and the elderly in Puskesmas Sobo District. The subjects' knowledge was assessed by comparing pre- and post-test scores, which included 10 questionnaire questions. We conducted an early detection program for children in grades 4-6 of elementary school, which included weight, height, blood pressure, saturation, heart sound screening, and a complete urine dipstick examination. 62 subjects participated in the community service, with Pre-Test Scores of 62.9±16.5 and Post-Test Scores of 71.7±20.2. There were 25 children examined in our community service, with 100% regular heart examination and 76% with trace proteinuria; systolic blood pressure 90 ± 11.7 mmHg and diastolic blood pressure 59.4 ± 11.6 mmHg. This community service initiative demonstrated its dual impact on enhancing health knowledge and facilitating the early detection of potential congenital abnormalities in children. The findings underscore the critical need for more systematic, comprehensive screening programs for kidney and heart health in children across the region.